ANALISIS PERBANDINGAN MANAJEMEN BANDWIDTH ANTARA METODE SIMPLE QUEUE DAN QUEUE TREE PADA KOPERASI KARYAWAN INDOCEMENT - Alvi Garaali P; Siti Faizah (Jupiter: Journal of Computer & Information Technology, 2022)
The mobility of internet users is now increasingly being used, many providers currently provide various variations of the bandwidth used for their users. Koperasi Karyawan Indocement requires the use of bandwidth aimed at making the internet network connection stable and reducing the error rate in the network connection. Bandwidth management regulates bandwidth limitation so that it is evenly distributed to each client between the simple queue and queue tree methods, the problem faced by the Koperasi Karyawan Indocement is that there is no bandwidth limit applied. This study aims to solve the problems faced in Koperasi Karyawan Indocement by comparing bandwidth management between the simple queue and queue tree methods. Where from the results of this study will be applied which method is better for allocating bandwidth evenly.